2016
DOI: 10.3389/fpls.2016.00480
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Phytochrome Signaling during Photomorphogenesis: From Physiology to Molecular Mechanisms and Back

Abstract: Light exposure results in distinct responses in specific seedling tissues during photomorphogenesis. Light promotes growth of cotyledons and leaves, as well as development and elongation of roots, whereas light inhibits elongation of hypocotyls. For distinct plant responses such as shade avoidance, far-red light or shifts in spectral light quality similarly have disparate impacts on distinct plant tissues, resulting in elongation of stems or petioles and a reduction in growth of leaf blades for many species. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 99 publications
(114 reference statements)
1
19
0
1
Order By: Relevance
“…Localized light reception, followed by inter-organ and intercellular signaling, was invoked in the light-dependent control of seedling development based on a variety of previous experimental approaches, yet the molecular basis has remained unidentified [7,34,55,56]. Thus, working models of the regulatory network controlling the switch from skotomorphogenic to photomorphogenic development have so far usually been depicted in a single cell.…”
Section: An Extracellular Cell-wall-derived Vsog Dark Signal Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized light reception, followed by inter-organ and intercellular signaling, was invoked in the light-dependent control of seedling development based on a variety of previous experimental approaches, yet the molecular basis has remained unidentified [7,34,55,56]. Thus, working models of the regulatory network controlling the switch from skotomorphogenic to photomorphogenic development have so far usually been depicted in a single cell.…”
Section: An Extracellular Cell-wall-derived Vsog Dark Signal Controlsmentioning
confidence: 99%
“…Localized illumination of seedlings, excision of seedling organs and cell-type-specific expression of transgenes in wildtype and mutant backgrounds provided complementary lines of evidence for non-cell-autonomous responses to light during photomorphogenesis [1,6,7]. The molecular basis of the implied cell-cell communication, however, has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the acceleration of flowering was not correlated with the enhancement of elongation growth under a low R:FR in more than 100 accessions of arabidopsis (Arabidopsis thaliana), showing that ecotypes that responded strongly in elongation did not necessarily respond strongly in floral acceleration, and vice versa (Botto and Smith, 2002). Recent molecular studies have demonstrated that responses in different organs triggered by the same light signal are from distinct signaling cascades downstream of the activated photoreceptors in distinct tissues (Montgomery, 2016). Therefore, increased stem elongation does not necessarily correlate with leaf expansion or stimulation of flowering.…”
Section: Introductionmentioning
confidence: 99%
“…Nízký poměr R/ FR spouští kaskádu různých morfogenních procesů, které pomáhají rostlině vyhnout se stínu a překonat konkurenci okolních rostlin. Pod vlivem nízkého , 2016;Tang & Liesche, 2017). Změny v modrém záření či UV-A a UV-B také podobně mění růstové a vývojové odpově-di rostlin i odpovědi na stresové faktory prostředí (více v přehledu Huche-Thelier et al, 2016).…”
Section: Fotoreceptory Pro Uv-b Záření: Fotoreceptor Uvr8unclassified